Distributed Control Scheme for Clusters of Power Quality Compensators in Grid-Tied AC Microgrids - Martínez-Gómez, Manuel; Burgos-Mellado, Claudio; Morales-Paredes, Helmo Kelis [UNESP]; Gómez, Juan Sebastián; Verma, Anant Kumar; Bonaldo, Jakson Paulo (MDPI, 2023)
Modern electrical systems are required to provide increasing standards of power quality, so converters in microgrids need to cooperate to accomplish the requirements efficiently in terms of costs and energy. Currently, power quality compensators (PQCs) are deployed individually, with no capacity to support distant nodes. Motivated by this, this paper proposes a consensus-based scheme, augmented by the conservative power theory (CPT), for controlling clusters of PQCs aiming to improve the imbalance, harmonics and the power factor at multiple nodes of a grid-tied AC microgrid. The CPT calculates the current components that need to be compensated at the point of common coupling (PCC) and local nodes; then, compensations are implemented by using each grid-following converter’s remaining volt-ampere capacity, converting them in PQCs and improving the system’s efficiency. The proposal yields the non-active power balancing among PQCs compounding a cluster. Constraints of cumulative non-active contribution and maximum disposable power are included in each controller. Also, grid-support components are calculated locally based on shared information from the PCC. Extensive simulations show a seamless compensation (even with time delays) of unbalanced and harmonics current (below 20% each) at selected buses, with control convergences of 0.5–1.5 [s] within clusters and 1.0–3.0 [s] for multi-cluster cooperation.
Keywords: AC microgrids; cluster control; conservative power theory; distributed control; power quality; smart grids